Meningkatkan Kemampuan Belajar Siswa Mengenal Rangka Manusia Pada Mata Pelajaran IPA Menggunakan Media Gambar Pada Siswa Kelas IV SD 1 Kristen - Arona Arona (Institute For Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
This study aims to determine the effect of using picture props on increasing students' learning abilities to recognize the human skeleton in science subjects in Grade IV students of SD 1 Kristen. This research is descriptive, meaning that it tries to explain the results of research from the effects of existing data processing. This study involved 26 fourth-grade students of SD 1 Kristen, who were carried out through 2 cycles. Cycle I and cycle II used the subject of the function of the human skeleton and its maintenance, each cycle following the stages of the Kemmis and Mc Taggart model, namely (1) planning, (2) implementing actions, (3) observing actions, (4) reflection of the actions to be carried out. Data were obtained through learning outcomes tests, observations and were analyzed using descriptive techniques. The results of data analysis showed that the ability to use the visual aids achieved good qualifications or (70-90 %) and the criteria for learning completeness—students well-received student responses to using picture props. Student learning outcomes taking the Pre-Test in the first cycle had an average of 63.62, while the second cycle had an average of 75.08. Student learning outcomes following the Post-Test in the first cycle had an average of 80.54, while in the second cycle, it had an average of 89.69. Increasing the learning outcomes obtained by these students was also supported by the result data. And from these results, it can be concluded that using picture props can improve students' learning abilities to recognize the human skeleton in science subjects in Grade IV students of SD 1 Kristen.